Repeated kidney re-transplantation in times of organ shortage – a critical review. Issue 1 (February 2021) - Assfalg, Volker; Hüser, Norbert
Abstract : Purpose of review: Organ shortage forces those responsible to streamline allocation rules to provide a maximum of candidates with a graft and to optimize transplant outcome. Recently, repeated kidney re-transplantation was investigated in several studies with different analytic settings concerning the control group, the donors, parameters influencing outcome, and demographic characteristics. This review gives an overview on the candidates awaiting a repeated re-transplantation, summarizes the outcome, and comments on the relevance of these findings in the context of sustained organ shortage. Recent findings: Repeated kidney re-transplantation is technically and immunologically feasible and the recipients' survival is better compared to candidates remaining on dialysis or on the waiting-list. However, the outcome is mainly reported to be worse as compared to first or second kidney transplantation. Kidneys from living donors seem to have a favorable impact on outcome in this setting. Summary: The survival benefit of repeated re-transplantation recipients over patients on dialysis demands for continuation of this procedure. Comprehensive registries are essential to continuously optimize allocation. Governmental authorities are obliged to set the course to increase organ donation rather than forcing transplant decision makers to withhold a third or fourth graft from any candidate.